Предмет: Математика,
автор: tupilenkomaha69
Спростіть вираз 6(-1х)-15(х-2)-12 та знайдіть значення якщо х=1
Ответы
Автор ответа:
0
Ответ:
-3
Пошаговое объяснение:
-6x-15x+30-12=-21x+18
Подставим х=1
-21*1+18=-21+18=-3
tupilenkomaha69:
Спасибо
Автор ответа:
0
6(-1х) -15(х-2)-12 = -6х-15х+30-12
х=1
-6×1-15×1+30-12= -6-15+30-12 = -3
Похожие вопросы
Предмет: Русский язык,
автор: 20007qw
Предмет: Английский язык,
автор: Deniska2020
Предмет: Українська мова,
автор: Skif05
Предмет: Литература,
автор: Cat132002